Anti-Cancer Activity Of The Combination Of Marine Mineral Consentrates And α Mangostin On Prostate Cancer Line DU 145 And HEK 293 By WST-8 Method - Giska Putri Agustina; Syafika Alaydrus; Niluh Puspita Dewi (Jurnal Penelitian Pendidikan IPA, 2024)
Marine mineral concentrates have good activity against normal cells, but are less effective against cancer cells. This research was carried out by combining concentrations of sea minerals with natural ingredients that have anti-cancer potential, one of which is α-mangostin. This study aims to determine the IC50 of the combination of α-mangostin, marine mineral concentrate, the combination of α-mangostin & marine mineral concentrate when compared cisplatin and evaluate the activity of α-mangostin, KML and the combination of α-mangostin and KML compared with ciplatin against the DU 145 cancer cell line and HEK 293. The method used is cytotoxicity testing using the WST-8 method. The results of the test materials were α-Mangostin 16.89 ppm, the combination of α-Mangostin-KML with a concentration of 12.5 ppm, namely 1,732 ppm, the combination of α-Mangostin-KML with a concentration of 25 ppm, namely 4,930 ppm, the combination of α-Mangostin-KML with concentration of 50 ppm 5,194 ppm, and cisplatin 4,649 ppm. The results of data analysis show significant differences for all samples. Conclusion α-Mangostin helps KML increase the cytotoxic effect on DU 145 cancer cells and sea mineral concentrate helps reduce the cytotoxic effect of α-Mangostin on normal HEK-293 cells.